UNUSUAL CATCH OF GHOL PSEUDOSCIAENA DIACANTHUS OFF GOA - Thomas, P A; Kunju, M M (Indian Journal of Fisheries, 2011)
O.n 19th September 1973, a huge shoal of 'Ghol' was caught by a privatepurse seiner off Goa. The total number of specimens captured was 2309 and thesize ranged from 95 to 130 cm. with an average length of 109 cm. The total weightof the catch was estimated at 30.24 tonnes and composed of V to VII year oldfish. Examination of stomach contemts revealed that the food item was MalabarSole Cynoglossus macrostomiis (Norman). Regurgitated food was found inside themouth, but extroverted stomach were not noted. The availability of food in theinshore waters off Goa is suggested as the prime factor in the inshore migration of"Ghol' during the monsoon months.